RETRACTED: Theoretical and methodological foundations for the development and formal model of behavior of a subject of a multi-level innovation environment with information asymmetry - Gurtuev Alim; Makhosheva Salima; Ivanov Zaur; Khadzhieva Mariyam (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001